Analisis Usabilty Antarmuka Halaman Kerja (Back Office) SLiMS Versi 8 Akasia Menggunakan Nielsen’s Attributes of Usability - Safira Almaida; Danang Dwijo Kangko; Wardiyono Wardiyono (Perpustakaan Nasional RI, 2022)
The purpose of this study was to measure and analyze usability evaluation on the SLiMS Version 8 Akasia work page interface using the Nilsen's Attributes of Usability questionnaire method which consists of 5 indicators, namely Learnibility (easy to learn), Efficiency (efficient), Memorability (easy to remember), Error (failure), and Satisfaction (satisfaction). This type of research is descriptive with a quantitative approach. The limit of this study only discusses the usability level of the SLiMS 8 Akasia back office interface, not only on other interface pages in the SLiMS Version 8 Akasia application. The samples chosen were staff or librarians who were accustomed to using the SLiMS Version 8 Akasia application to support their daily work. The results of tabulation and analysis of respondent data stated their agreement on each indicator statement of Learnibility, Efficiency, Memorability, and Satisfaction. Meanwhile, respondents stated that the answer was neutral on the Error indicator